Cálculo de distâncias inacessíveis : uma viagem astronômica - Hoffmann, Paula (My University, 2025)
This dissertation investigated how a Learning Unit contextualized through Astronomy can contribute to the development of trigonometric thinking in high school students, focusing on the calculation of inaccessible distances. The proposal was grounded in Vigotski's socio interactionist theory and structured based on the Three Pedagogical Moments, combining history, practice, simulation, and experimentation. Three objectives were analyzed: (1) to identify whether students recognize the elements necessary for calculating inaccessible distances; (2) to evaluate the application of trigonometric ratios; and (3) to investigate students' understanding of the parallax concept. Data were collected through diagnostic assessments, practical activity records, and a final questionnaire. The results revealed significant transitions in students' levels of conceptual understanding, with most reaching the Zone of Actual Development by the end of the Learning Unit. As an outcome of the research, two didactic notebooks were developed - one for students and another for teachers - containing step-by-step guidance, QR codes, and mediation suggestions to facilitate replication in diverse school contexts. The experience showed that an interdisciplinary, practical, and historically grounded approach enhances engagement, meaning-making, and content retention in mathematics learning. [resumo fornecido pelo autor]
Esta dissertação investigou de que forma uma unidade de aprendizagem contextualizada pela Astronomia pode contribuir para o desenvolvimento do pensamento trigonométrico de estudantes do Ensino Médio, com foco no cálculo de distâncias inacessíveis. A proposta foi fundamentada na Teoria Sociointeracionista de Vigotski e estruturada a partir dos Três Momentos Pedagógicos, combinando história, prática, simulação e experimentação. Foram analisados três objetivos: (1) identificar se os estudantes reconhecem os elementos necessários para o cálculo de distâncias inacessíveis; (2) avaliar a aplicação das razões trigonométricas; e (3) investigar a compreensão do conceito de paralaxe estelar. Os dados foram coletados por meio de instrumentos diagnósticos, registros de atividades práticas e questionário final. Os resultados revelaram transições significativas nos níveis de significação dos estudantes, com predominância da Zona de Desenvolvimento Real ao final da Unidade de Aprendizagem. Como produto da pesquisa, foram elaborados dois cadernos didáticos -um voltado ao aluno e outro ao professor -com orientações, QR Codes e sugestões de mediação, com o intuito de tornar a proposta replicável e viável para diferentes realidades escolares. A experiência evidenciou que a abordagem interdisciplinar, prática e histórica promove maior engajamento, significação e consolidação do conteúdo matemático. [resumo fornecido pelo autor]
Keywords: Trigonometria; Matemática - Estudo e ensino; Astronomia; Aprendizagem; Vigotsky, Lev Semenovich, 1896-1934; Trigonometry; Mathematics - Study and Teaching; Astronomy; Learning